Penerapan Prinsip Hukum Internasional dan Urgensi Pemahaman English Law dalam Proyek Infrastruktur Antar Negara (Studi Normatif atas Proyek Konstruksi Berbasis Pembiayaan Asian Development Bank) - Yulistiawati, Wina; Sami’an, Sami’an; Hardjomuljadi, Sarwono (Syntax Corporation, 2026)
Cross-border infrastructure projects involve complex interactions between domestic legal systems, public international law, and transnational contractual frameworks. Such projects are commonly financed by multilateral development banks and implemented under international standard contracts, particularly FIDIC, which in practice are frequently governed or interpreted through English law principles. This article examines the application of international legal principles in cross-border infrastructure projects and analyzes the critical importance of English law literacy for public authorities and contractors originating from civil law jurisdictions. Using a normative juridical method with conceptual and comparative law approaches, this study demonstrates that the dominance of English law in FIDIC-based contracts and international dispute resolution mechanisms makes compliance with procedural doctrines—such as condition precedent, strict notice requirements, and the prevention principle—decisive for the success of contractual claims and risk management. Focusing on the normative framework of construction projects financed by the Asian Development Bank (ADB), the study concludes that a sound understanding of English law is not merely complementary but constitutes a strategic legal necessity for ensuring legal certainty, equitable risk allocation, and effective dispute resolution in cross-border infrastructure development.